Post-Translational Modification of PTEN Protein: Quantity and Activity - Li, Xiao; Yang, Pu; Hou, Xiaoli; Ji, Shaoping (Oncology Reviews, 2024)
Post-translational modifications play a crucial role in regulating protein function and stability. PTEN is a crucial tumor suppressor involved in regulating cellular proliferation, survival and migration processes. However, dysregulation of PTEN is common in various human cancers. Its stability and activation/suppression have been extensively studied in the context of tumorigenesis through inhibiting PI3K/AKT signaling pathway. PTEN undergoes diverse post-translational modifications, primarily including phosphorylation, acetylation, ubiquitination, SUMOylation, neddylation and oxidation, which finely tune PTEN activity and stability. Generally, phosphorylation can modulate PTEN's activity by affecting its lipid phosphatase function, leading to an altered power of the signaling pathways. Acetylation influences PTEN protein stability and degradation rates. SUMOylation has been implicated in PTEN localization and interaction with other proteins, affecting its overall function. In addition, neddylation, as a novel modification of PTEN, is also a key regulatory mechanism for the loss of tumor suppressor function of PTEN. Although current therapeutic approaches focus primarily on inhibiting PI3 kinase, understanding the post-translational modification of PTEN could help provide new therapeutic strategies that restore PTEN's role in PIP3-dependent tumors. In this review, we will summarize the major recent progress in regulation of PTEN protein level and activity. Finally, we hope that these insights will contribute to a better understanding of this critical tumor suppressor and its potential implications for cancer therapy in future.